Peranan Pembimbing Kemasyarakatan Terhadap Kasus Kekerasan Oleh Anak - Riyadi R (Madani: Jurnal Ilmiah Multidisiplin, 2023)
Violent crimes that occur in Indonesia are mostly committed by children. Violence that occurs can be detrimental to victims who experience it, ranging from minor to serious injuries, then disability that can be suffered even to death. The Criminal Law Code threatens with high prison sentences, but children have their own criminal justice system, namely with the existence of Restorative Justice in accordance with what is stated in Law Number 11 of 2012 concerning the Juvenile Criminal Justice System by resolving the case through diversion. One of the roles which carry out diversion is the Community Officer. Community officers have duties and functions to help fulfilled rights and accompany children who commit crimes by seeking information to achieve diversion from the start of diversion at the request of investigators through a complete community information report prepared by the Community Officer. The role of Community Officers is in 3 stages, namely the stage before trial (Pre-adjudication), the stage during the trial (adjudication) and the stage after trial (post-adjudication). The role of Community Officers against Children Against the Law/committing crimes is very important and necessary, this is because Probation Officers have their own techniques and methods supported by the authority they have in handling Children Faced with the Law based on existing regulations.